PENGARUH KOMPETENSI, MOTIVASI DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL SEKECAMATAN RANGKUI KOTA PANGKALPINANG - Citra Nur Vania; Hamsani; Reniati (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the influence of competence, motivation, and work facilities on the performance of Civil Servants (PNS) in Rangkui District, Pangkalpinang City. The background of the research is grounded in the importance of improving the performance of government apparatus through strengthening human resources and providing a supportive work environment. This research adopts a quantitative approach with an associative method. The sample consists of all 60 civil servants in the district, selected using the total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that competence, motivation, and work facilities each have a positive and significant partial effect on employee performance. Simultaneously, these three variables contribute 66.7% to the variation in civil servant performance, while the remaining 33.3% is explained by other variables outside the scope of this study. These findings indicate that improving employee performance cannot be separated from strengthening competence, increasing motivation, and providing adequate work facilities.